Pharmacological and mechanical properties of isolated pig coronary veins - Wang, Bowen; Qin, Zhi; Li, Mei; Arner, Anders; Steen, Stig (Frontiers in Physiology, 2023)
Recent successful cardiac transplantation from pig to non-human primates and the first pig-to-human transplantation has put the focus on the properties of the pig heart. In contrast to the coronary arteries, the coronary veins are less well characterized and the aim was to examine the mechanical and pharmacological properties of coronary veins in comparison to the arteries. Vessel segments from the left anterior descending coronary artery (LAD) and the concomitant vein were isolated from pig hearts in cardioplegia and examined in vitro. The wall thickness, active tension and active stress at optimal circumference were lower in coronary veins, reflecting the lower intravascular pressure in vivo. Reverse transcription polymerase chain reaction (RT-PCR) analysis of myosin isoforms showed that the vein could be characterized as having a slower smooth muscle phenotype compared to the artery. Both vessel types contracted in response to the thromboxane agonist U46619 with EC50 values of about 20 nM. The artery contracted in response to acetylcholine. Precontracted arteries relaxed in noradrenaline and substance P. In contrast, the veins relaxed in acetylcholine, contracted in noradrenaline and were unresponsive to substance P. In conclusion, these results demonstrate significant differences between the coronary artery and vein in the smooth muscle properties and in the responses to sympathetic and parasympathetic stimuli.